DESIGN IN RENTAL RENTAL SYSTEM ADMINISTRATION USING VCD ZAZU MICROSOFT ACCESS 2000 - Dita Puspitasari; Yulina, SKom, MMSI Yulina, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Management data processing that runs during the dirental VCD Zazu is still done manually. So that the services provided to its customers was very unsatisfactory. The use of computers as a means to overcome the weakness - weakness of the data processing is done manually one of them is that in the process the desired data processing becomes more orderly progress to support these rentals. Thus the meeting obtained by the correct data, reliable and timely.